Análise exergética, exergoeconômica e exergoambiental de um sistema de trigeração auxiliado por energia solar - Ferreira, João Victor Mendes (2021)
This work discusses the exergy, exergoeconomic and exergoenvironmental analyses applied on a trigeneration system. A natural gas engine produces electrical power and its waste heat is recovered to drive a mixed effect H2O-LiBr absorption chiller and heat exchanger to produce cooling and hot water. A solar system composed of evacuated tube collectors with two tanks assists the trigeneration system. The thermodynamic model of the system was developed on EES software, based on mass and energy conservation principles. The exergy analysis considered physical and chemical exergies. The exergoeconomic model follows the SPECO approach and the exergoenvironmental analysis utilizes Ecoindicator 99 method. The research aims to model the trigeneration system and to assess the exergy, economic and environmental performance. Circulation pump and solar system present the lowest exergy efficiencies. The exergy efficiency of the absorption chiller decreases until 15°C, reaching its highest value at 10°C due the change in definitions of product and fuel. Investments in order to optimize the high pressure generator are cost-effective. On an exergoenvironmental viewpoint, the pump and low pressure generator 2 presented the worst performances and gas engine was responsible by 81,89% of total environmental impact rate, mainly due NO emission. The costs and environmental impacts per exergy unit of the products were obtained. The exergoeconomic and exergoenvironmental approaches have identified critical components and the main costs and environmental impact sources of the system.